Aplikasi Plant Structure Introduction Learning Application for Early Childhood using Augmented Reality - Pratiwi, Adinda Putriani; Riyanto, Joko (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Pemanfaatan Teknologi Informasi (TI) dalam proses penyampaian informasi mengalami perkembangan pesat. Saat ini, teknologi terbaru yang digunakan dalam penyampaian informasi adalah teknologi Augmented Reality (AR). Pada teknologi AR, pengguna dapat menvisualisasikan objek dalam bentuk 3 dimensi. AR memiliki kelebihan bersifat interaktif dan real time sehingga AR banyak diimplementasikan di berbagai bidang. Di dunia pendidikan, AR digunakan sebagai media untuk mengenalkan struktur dan fungsi tumbuhan, terlebih mengenai mata pelajaran IPA yang terkesan susah dipahami di kalangan para pelajar. Media pembelajaran Augmented Reality Struktur dan Fungsi Tumbuhan dibuat melalui android menggunakan Unity 3D dengan Vuforia, dan menggunakan bahasa pemrograman C#, serta untuk design tampilan aplikasi menggunakan software 3D Studio Max. Dan untuk metode pengembangan perangkat lunak yang digunakan adalah waterfall. Untuk pengujian aplikasi yang dilakukan menggunakan Blackbox. Hasil dari penelitian ini adalah menjadikan proses belajar-mengajar peserta didik lebih interaktif dan inovatif. Plant Structure Introduction Learning Application for Early Childhood using Augmented Reality Abstract: Utilization of Information Technology (IT) in the process of delivering information has developed rapidly. Currently, the latest technology used in the delivery of information is Augmented Reality (AR) technology. In AR technology, users can visualize objects in 3-dimensional form. AR has the advantage of being interactive and real time so that AR is widely implemented in various fields. In the world of education, AR is used as a medium to introduce the structure and function of plants, especially regarding science subjects which seem difficult to understand among students. Learning media for Augmented Reality Structure and Function of Plants is made using Android using Unity 3D with Vuforia, and using the C# programming language, as well as for application display design using 3D Studio Max software. And for the software development method used is the waterfall. For application testing carried out using Blackbox. The result of this research is to make the teaching and learning process of students more interactive and innovative. Keywords: Augmented Reality, Plant Structure and Function, Unity 3D, Vuforia, Waterfall.